2011
DOI: 10.5194/osd-8-1575-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eddy characteristics in the Northern South China Sea as inferred from Lagrangian drifter data

Abstract: Cyclones and anticyclones from large scale to submesoscale on the Northern South China Sea (NSCS) have been statistically characterized based on the satellite-tracked Lagrangian drifter data using a geometric eddy identification method. There are totally 1972 eddies identified, 4/5 of which are anticyclonic eddies. If the submesoscale eddies are eliminated, the other eddies in the NSCS will show a 1.1–1 dominance with the number (133) of anticyclones over the number (122) of cyclones. The spatial distr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The values of M(t) in regions 3-5 are negative at small time lags but become positive at large time lags, indicating that these regions are dominated by anticyclonic eddies at small scales but by cyclonic circulations (e.g., mean flow) at large scales. These results are consistent with previous eddy-related studies over the SCS (e.g., Li et al 2011;Wang et al 2003;Xiu et al 2010). Using satellite altimeter data, Wang et al (2003) showed that the southwest of Taiwan (roughly region 2) is dominated by anticyclonic eddies (see their Fig.…”
Section: B Lagrangian Scales and Diffusivitysupporting
confidence: 93%
See 3 more Smart Citations
“…The values of M(t) in regions 3-5 are negative at small time lags but become positive at large time lags, indicating that these regions are dominated by anticyclonic eddies at small scales but by cyclonic circulations (e.g., mean flow) at large scales. These results are consistent with previous eddy-related studies over the SCS (e.g., Li et al 2011;Wang et al 2003;Xiu et al 2010). Using satellite altimeter data, Wang et al (2003) showed that the southwest of Taiwan (roughly region 2) is dominated by anticyclonic eddies (see their Fig.…”
Section: B Lagrangian Scales and Diffusivitysupporting
confidence: 93%
“…The angular momentum analysis for the asymmetric parts of the diffusivity tensor (k 12 and k 21 ) indicates that, in some regions (including the east and the northwest of the Luzon Strait and the exit region of Mekong River), the flows are dominated by anticyclonic eddies, while in other regions, such as the northern SCS, the flows are characterized by anticyclonic eddies at small scales but by cyclonic circulations at large scales. These results are consistent with previous eddy studies (e.g., Li et al 2011;Wang et al 2003;Xiu et al 2010), indicating that the computation of asymmetric parts of diffusivity tensor could be a valuable tool in accessing eddy features.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The analysis of eddy polarity by Chen et al [2011] also showed that there were more CEs than ACEs generated southwest of Taiwan. Li et al [2011] used drifter data from 1979 to the present to identify eddies in the northern SCS. Because of its sparse coverage compared with satellite altimeter data, drifter data might miss many eddies.…”
Section: Resultsmentioning
confidence: 99%